Quantification of brake data acquired with a brake power meter during simulated cross-country mountain bike racing - Miller, M. C.; Fink, P. W.; Macdermid, P. W.; Stannard, S. R. (Sports Biomechanics, 2019)
There is currently a dearth of information describing cycling performance outside of propulsive and physiological variables. The aim of the present study was to utilise a brake power meter to quantify braking during a multi-lap cross-country mountain bike time trial and to determine how braking affects performance. A significant negative association was determined between lap time and brake power (800.8 ± 216.4 W, mean ± SD; r = -0.446; p < 0.05), while the time spent braking (28.0 ± 6.4 s) was positively associated with lap time (314.3 ± 37.9 s; r = 0.477; p < 0.05). Despite propulsive power decreasing after the first lap (p < 0.05), lap time remained unchanged (p > 0.05) which was attributed to decreased brake work (p < 0.05) and brake time (p < 0.05) in both the front and rear brakes by the final lap. A multiple regression model incorporating braking and propulsion was able to explain more of the variance in lap time (r2 = 0.935) than propulsion alone (r2 = 0.826). The present study highlights that riders` braking contributes to mountain bike performance. As riders repeat a cross-country mountain bike track, they are able to change braking, which in turn can counterbalance a reduction in power output. Further research is required to understand braking better.